2017
DOI: 10.1590/s1679-87592017136606503
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability in populations of the fiddler crab Leptuca uruguayensis (Nobili, 1901) (Crustacea, Decapoda, Ocypodidae) from South America

Abstract: A comparative study on size and shape of Leptuca uruguayensis was carried out between populations from Garças River, Brazil (BP), and Solís Grande River, Uruguay (UP). The size of the onset of sexual maturity was also estimated for UP. A total of 36 crabs BP and 387 crabs UP were analyzed. In the relative growth analysis, carapace width (CW) for both sexes, major cheliped length (LMC) for males and abdomen width (AW) for females were measured. The centroid size of carapace (1.40±0.19 cm BP and 1.88±0.30 cm UP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…comm. ), while in Uruguayan estuaries L. uruguayensis inhabit stream lowlands (Masunari et al 2017).…”
Section: Distributionmentioning
confidence: 98%
See 1 more Smart Citation
“…comm. ), while in Uruguayan estuaries L. uruguayensis inhabit stream lowlands (Masunari et al 2017).…”
Section: Distributionmentioning
confidence: 98%
“…Small crabs: males with CW up to 12.0 mm in a population from Itacuruçá mangrove, Sepetiba Bay, southeastern Brazil (Bedê et al 2008). Leptuca uruguayensis, however, can attain up to 19.5 mm CW in the population from Solís Grande River, Uruguay (Masunari et al 2017).…”
Section: Subfamily Gelasiminaementioning
confidence: 99%
“…The allometric analysis showed that males acquired a larger average body size than females for the G. cruentata population captured in a tropical estuarine mangrove, and the same growth pattern was also described by Botelho et al (2004). Accord- ing to Masunari et al (2017), the size variation between the sexes can be explained by differentiated reproductive needs, as size dominance in male crabs increases opportunities for victory during intraspecific competition, courtship and handling the female during copulation.…”
Section: Linear Morphometrymentioning
confidence: 99%